PELATIHAN DAN PENDAMPINGAN KADER LOKAL DALAM PEMBERDAYAAN DAN PENGEMBANGAN KEGIATAN KEISLAMAN DI KECAMATAN NGRAYUN KABUPATEN PONOROGO - Mahfud Saiful Ansori; Amir Mukminin (Jurnal Al Basirah, 2021)
A fact that the religious life of the Muslim community in Indonesia can be seen in the existence of mosques, which mostly rest on religious and social religious activities. The mosque is a symbol that creates a communal identity as a binding to the collective life of the surrounding community which is appreciated in a variant of the relationship between congregation and various religious activities. This indicates that the social relations of Muslims are metamorphosed in the mosque. The function of a mosque is a miniature development of uluhiyah and human values. However, today only certain mosques develop this function and role. From a historical perspective, the mosque cannot be separated from the origin of Islam being propagated. This study uses a qualitative approach with data collection techniques by means of interviews, observations and documentation techniques, while the results of this study are 1) Community Condition of the Nurul Huda Mosque, Selur Village, Kec. Ngrayun Kab. Pononorogo, variously, the researchers classified there are three levels of society, namely the level of education, the level of the economy and the community's understanding of religion. 2) Empowerment activities in the area of ​​the Nurul Huda Mosque, Selur Ke Village. Ngrayun Kab. Pononorogo.Majlis Ta'lim AT-Taqwa which was founded by Erna Soekarno in 2016 with the aim of establishing it for community development and empowerment through the religious and economic sector of TPA Nurul Hidayah Al-Quran Education Park Nurul Hidayah was founded in 1993 by the pioneer and founder of this TPA Erna Sekarno's mother, she is a native of the Putuk hamlet, the village of all the Ponorogo regencies. The learning system is carried out 4 times a week, namely Monday, Thursday, Friday and Saturday with learning hours starting at 13.00-17.00 WIB. With the material being taught, Read and Write AL-QURAN, Pasholatan, Daily Prayers for children, morals and also learning Arabic. TK PAS An-nur His goal is to establish TK PAS AN-Nur as if he only established TPA Nurul Hidayah but this is a formal institution. TK PAS AN-Nur with a learning system Monday 3) Strategic Steps for Local Cadres in Improving Nurul Huda Mosque Selur Village Ke. Ngrayun Kab. Ponorogo There are strategic steps taken by local cadres in enhancing the empowerment of the mosque environment, namely commitment development, awareness development, education and training development, marketing to help poor families, problem solving consultations.